A Comparison of Two Forced Moulting Techniques (Journal of Science and Technology, 2016)
No forced moulting techniques were compared in a 16-week experiment using seventy-two 20-month-old Bosbek hybrid laying hens. In forced moulting technique-I (FMT-I), thirty -six birds were fasted for four days and fed ground maize ad libitum from day five today 30. In forced moulting technique-2 (FAIT' 2), 36 hens were fasted for ten days and fed ground maize ad libitum from day 11 to day 30. All birds on both techniques received natural daylight and water without restriction. Moulting was more rapid and complete in birds on PMT-2 than in those on P7‘1711. Post-moult hen-day egg production of hens on F71T-2 was significantly higher than that of hens on FMT- I (P < 0 01.) and was consistently higher during each of the twelve weekly post moult periods considered. Mean values of egg weight, shell thickness and Haugh unit scores did not differ significantly (P>0. 05) over the period.